Analysis of heavy metal contamination of soft tissues of bivalve mollusks in water bodies of Gomel and adjacent territories - Makarenko, Tatyana V.; Khadanovich, Albina V.; Pyrkh, Olga V.; Parfenkova, Anastasia S. (Journal of the Belarusian State University. Ecology, 2022)
Currently, observations of the components of aquatic ecosystems - hydrobionts and bottom sediments with the ability to deposit pollutants - are of particular importance. Comprehensive studies of the behavior of heavy metals in aquatic ecosystems are relevant and make it possible to provide an integral assessment of the state of the water body, determine the probability of secondary pollution, find out the migration paths of pollutants, and therefore their implementation is relevant. The article deals with the analysis of quantitative data on the content of heavy metals in the soft tissues of mollusks living in the reservoirs of Gomel and adjacent territories. An array of data was obtained for the period of research in 2010-2021, on the basis of which the choice of an ordinary pearl barley (Unio pictorum L.) as an object of monitoring studies of the ecological state of water bodies was justified. The change in the content of copper, lead and nickel in the tissues of the studied mollusk species during the period of research from 2010 to 2021 indicates a change in the physicochemical conditions in the studied reservoirs, as well as a change in the content of biologically accessible metal forms in water and bottom sediments of aquatic ecosystems. This fact confirms the presence of different routes of entry of heavy metals into the body of different species of bivalve mollusks, as well as the different availability of metal compounds in components of the same aquatic ecosystem for different species of mollusks. As a result of the analysis of the array of data obtained from 2010 to 2021, the authors determined the background concentrations of heavy metals in the tissues of common pearl barley living in the reservoirs of Gomel and adjacent territories: for lead - 0.17 mg/kg, zinc - 19.20 mg/kg, copper - 0.71 mg/kg, manganese - 1084.22 mg/kg, cobalt - 0.25 mg/kg, chromium - 0.71 mg/kg, nickel - 0.95 mg/kg. Patterns of change in the quantitative content of heavy metals in the soft tissues of molluscs are shown.